EKONOMI REGIONAL PROVINSI SULAWESI TENGGARA: Pendekatan Sektor Basis dan Analisis Inputâ€Output - Subanti, Sri; Hakim, Arif Rahman (Jurnal Ekonomi & Studi Pembangunan, 2009)
This paper aims to study regional economic in Southeast Sulawesi Province. Analyse in this paper used export based approach and input-output analysis. This study found that (1) agriculture sector, construction, transport and communication, and service sector become base sectors in Southeast Sulawesi. (2) Sector electricity, gas, water and sector finance have positive value in industry mix and regional shift. Otherwise, sector agriculture and sector services can categorize in slow growth sector and high competence sector. (3) Sector mining have highest output multiplier. (4) Sector agriculture and sector trade, hotel, restaurant have forward linkage indeks more than one. (5) Sector mining, sector agriculture, and sector trade hotel restaurant have backward linkage indeks more than one too. (6) Sector agriculture and sector trade hotel restaurant become key sectors in Southeast Sulawesi Province. This sectors which need to be developed because by expanding this sector expected to push another economic sector.